Efeitos do treinamento esportivo periodizados sobre as variáveis antropométricas, capacidades físicas, hemodinâmicas e a Pressão Intracraniana (PIC) de atletas profissionais - Teixeira, Jeferson Américo Ancelmo (2022)
Periodization in sports training is always questioned, as well as the effects on the individual on the physical aspects represented by anthropometric and hemodynamic capabilities. In particular, the behavior of intracranial pressure has been shown to be a vital new variable for brain functioning and still little elucidated in the field of training. Thus, the present study aimed to evaluate the effects of a periodization of physical training with professional athletes in the modalities of men's soccer, futsal and women's volleyball during 10 weeks in three stages pre-season (v0), after 5 weeks (v1) and after 10 weeks (v2). For this, anthropometric, hemodynamic and physical tests were performed. As for the anthropometric variables, BMI and %F, the three modalities had an evolution, that is, a reduction in the values, in the scope of the physical capacities there was also a significant improvement over the 10 weeks highlighting the increase in VO2max., increase in potency of the vertical jump and reduction in the time of the agility test. As for the hemodynamic variables, in addition to the reduction in BP, it was possible to verify a reduction in the values of ICP and HRV, with a relationship of greater action of the parasympathetic system in relation to the sympathetic one. Therefore, we conclude that the effect of periodization was positive for the 3 modalities, in addition to promoting a change in ICP pressure values and actions of sympathetic and parasympathetic activities.